Characterization of school adolescent students with suicide risk in Medellin, 2006 - Diana C. Toro G; Ramón E. Paniagua S; Carlos M. González P; Brígida Montoya G (Universidad de Antioquia, 2009)
Objective: To explore the possible association between the risk of suicide, depression, consumption of psychoactive and family dysfunction in school adolescents. Methodology: It was administered a self-administered survey to a random sample of 779 adolescents to assess the risk of suicide, depression, psychoactive substance use and family dysfunction, the instruments were used ISO-30, CDI-LA-II CIDI and Family Apgar respectively. The analysis used the technique of case-control method. Results:The prevalence of suicide risk was between 23.0% and 26.5%. Depression and family dysfunction were positively associated with suicide risk, with a disparity ratio of 4.3 and 2.0 respectively. Conclusions: The results show the magnitude of a problem that must take into account the educational authorities, the municipal administration and parents. A priority is to strengthen programs for adolescent depression screening, and also require to the State better treatments for depression (not just limited to the drug). We must promote the strategy of school parents in educational institutions, emphasizing issues related to mental health and stress the importance of communication, cooperation, affection and respect among family members.